Large ovarian mucinous cystadenoma in premenarchal girl - a case report - Pramod S; Katragadda Satya Vani (Barpeta Obstetrics and Gynaecological Society, 2018)
Most common ovarian mass in children is benign functional cyst. Epithelial tumors account for 8-10% of ovarian tumors. Most common epithelial tumor is cystadenoma. Mucinous cystadenoma occurs in 3rd - 6th decade of life. We report a case of 10 years old premenarchal girl presenting with abdominal distension and discomfort. On examination the entire abdomen was occupied by a firm mass. CT imaging showed a large multiloculated cystic lesion arising from the right ovary. The child underwent right salphingo-oophrectomy. The biopsy of the mass was suggestive of benign mucinous cystadenoma. The child was on regular follow up. After 1 year of follow up child is doing well.